Promoting hot debriefing in an emergency department. Issue 3 (16th August 2020) - Gilmartin, Stephen; Martin, Laura; Kenny, Siobhain; Callanan, Ian; Salter, Nigel
Abstract : Introduction: Debriefing is a process of communication that takes place between a team following a clinical case. Debriefing facilitates discussion of individual and team level performance and identifies points of excellence as well as potential errors made. This helps to develop plans to improve subsequent performance. While the American Heart Association and the UK Resuscitation Council recommend debriefing following every cardiac arrest attended by a healthcare professional, it has not become part of everyday practice. In the emergency department (ED), this is in part attributable to time pressures and workload. Hot debriefing is a form of debriefing which should occur 'there and then' following a clinical event. The aim of this quality improvement project was to introduce hot debriefing to our ED following all cardiac arrests. Methods: A hot debriefing tool was designed following simulated cardiac arrest scenarios and team feedback. This tool was then introduced to the ED for use after all cardiac arrests. The team lead was asked to complete a debrief form. These completed hot debrief forms were collated monthly and compared with the department's cardiac arrest register. Any changes made to cardiac arrest management following hot debriefing were recorded. Qualitative feedback was obtained through questionnaires. Results: During the 6-month study period, 42% of all cardiac arrest cases were followed by a hot debrief. Practice changes were made to resus room equipment, practitioners' non-technical skills and the department's educational activities. 95% of participants felt the hot debriefing tool was of 'just right' duration, 100% felt the process helped with their clinical practice, and 90% felt they benefited psychologically from the process. Conclusion: The introduction of a hot debriefing tool in our department has led to real-world changes to cardiac arrest care. The process benefits participants' clinical practice as well as psychological well-being.